Determination of Trantinterol Enantiomers in Human Plasma by High‐Performance Liquid Chromatography – Tandem Mass Spectrometry Using Vancomycin Chiral Stationary Phase and Solid Phase Extraction and Stereoselective Pharmacokinetic Application. Issue 5 (17th March 2015) - Qin, Feng; Wang, Yanjuan; Wang, Lijuan; Zhao, Longshan; Pan, Li; Cheng, Maosheng; Li, Famei
Abstract A sensitive and enantioselective vancomycin chiral stationary phase high‐performance liquid chromatography–tandem mass spectrometry method was developed for the determination of trantinterol enantiomers in human plasma. Baseline resolution was achieved using the vancomycin chiral stationary phase known as Chirobiotic V with polar ionic mobile phase consisting of acetonitrile–methanol (60:40, v/v) containing 0.01% ammonia and 0.02% acetic acid at a flow rate of 1.0 mL/min. Waters Oasis HLB C18 solid phase extraction cartridges were used in the sample preparation of trantinterol samples from plasma. The detection was performed on a triple‐quadrupole tandem mass spectrometer by multiple reaction monitoring mode via electrospray ionization. The calibration curve was linear in a concentration range from 0.0606 to 30.3 ng/mL in plasma, with the lower limit of quantification of 0.0606 ng/mL. The intra‐ and interday precision (relative standard deviation) values were within 9.7% and the accuracy (relative error) was from −6.6 to 7.2% at all quality control levels. The method was successfully applied to a study of stereoselective pharmacokinetics in human. Chirality 27:327–331, 2015.© 2015 Wiley Periodicals, Inc.